Election Night as Bruce Bronzan Wins 31st Assembly District Primary - Watkins, Howard::::::::: (1982)
Chloe Bronzan, Adam Watkins, Bruce Bronzan, Linda Bronzan in front of old Fresno photograph Old Courthouse and Hughes Hotel in photograph